2008
DOI: 10.1108/14676370810842184
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in higher education in Atlantic Canada

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 3 publications
0
58
2
4
Order By: Relevance
“…However, our review illustrates that while a number of innovative sustainable approaches to university operations are detailed in the reviewed literature on North American universities and colleges, the operations policies appear much more piecemeal and inconsistent than in either East Asia or Europe. For example, Beringer et al [47] summarize that sustainability in physical operations for institutions in Atlantic Canada remains largely unaddressed. In a study of American institutions, it was found that historically California's PSE institutions have led the charge for sustainable building operations in US post-secondary education [48].…”
Section: Comparing Campus Operations Policiesmentioning
confidence: 99%
“…However, our review illustrates that while a number of innovative sustainable approaches to university operations are detailed in the reviewed literature on North American universities and colleges, the operations policies appear much more piecemeal and inconsistent than in either East Asia or Europe. For example, Beringer et al [47] summarize that sustainability in physical operations for institutions in Atlantic Canada remains largely unaddressed. In a study of American institutions, it was found that historically California's PSE institutions have led the charge for sustainable building operations in US post-secondary education [48].…”
Section: Comparing Campus Operations Policiesmentioning
confidence: 99%
“…The importance of the role of institutions can also be significant because ìif the role of colleges and universities is to educate members of the society, then they must be an active instrument of sustainable movementî (Beringer, Malone, andWright, 2006, p. 1). Molina, Fernandez-Sainz andIzaguirre-Olaizola (2013, p. 13) proved in their research conducted at four universities that formal education and knowledge of environmental problems clearly affected pro-environmental behavior, but in a very complex way.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sustainability has become an increasingly important issue for universities worldwide (Beringer et al, 2008). Some of the initiatives are directed by government's legislative framework (Axelsson et al, 2008).…”
Section: Incorporation Of Sustainability Within the Higher Education mentioning
confidence: 99%